ANALISIS PENERAPAN TARGET COSTING SEBAGAI SISTEM PENGENDALIAN BIAYA PRODUKSI PADA CV.VEREL TRI PUTRA MANDIRI - Sumakul, Anggreini Merry; Manossoh, Hendrik; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2018)
Target costing method is one of the good method which used in efforts to decrease cost production. With the efficiency of production cost, the profit in the company then will increase. There are 3 stages to derect the implementation of target costing which are to calculate the production cost based on the company’s calculate, to execute value engineering and aply it unto the calculate of production cost. This study aims to determine does the impelementation of target costing is effecting enough as one of the effortsto controlling the production cost in CV.Verel Tri Putra Mandiri. The result shows that with the implementing target costing in CV.Verel Tri Putra Mandiri on controlling to awards cost production is proved to be better than with the method the company’s used all this time. Therefore, the conclusion for this research is that the company’s should using the target costing method in order to make the production cost be more efficient and so the profit or again which company’s eager to achive will be more likely to succed.Keyword : Target Costing